The Effect of Workshop Training Method and Electronic Teaching Method on Mathematics Learning - Safari, Azam; Dr. Zahra Hosseini (European Journal of Multidisciplinary Studies, 2016)
The present study with the aim to investigate the effect of training by using of electronic content and workshop method on math learning of high school students of eighteen region of Tehran has been done. The research method was applied and quasi-experimental with pretest-posttest design and control group. The study population included all girl students studying at second year of high school in public schools of eighteen region of Tehran in the 94-95 school year that by using of sampling method three classes were selected. The first experimental group with electronic content and the second experimental group by using of workshop method were trained that with the control group, who were trained in the traditional way, were compared. To determine the effect of work of education on math learning in the three groups, the analysis of covariance and ANOVA were used. The results showed that math scores in the two experimental groups were higher than the control group. Also, comparing the post test scores of math learning in the two experimental groups showed that the training by using of workshop method more than training with electronic content has effect on math learning.
Keywords: electronic content, workshop method, learning